Morphological Model of Derivational Patterns of Fi‘il Tsulāthī Mujarrad: Integration of Classical And Modern Linguistics - Alif Cahya Setiyadi; Moh. Ismail; Luthfi Muhyiddin (Asalibuna, 2025)
This study explores the derivational patterns of fi‘il tsulāthī mujarrad, the unaugmented trilateral verb roots that form the foundation of Arabic morphology, by integrating insights from classical Arabic grammar and modern linguistic theory. Classical grammarians such as Sībawayh, Ibn Mālik, and al-Zamakhsharī offered detailed descriptions of verb patterns (awzān) like fa‘ala, fa‘ila, and fa‘ula, categorizing them based on nuanced semantic functions such as transitivity, stativity, and intensity. While these classical frameworks provide valuable semantic depth, they often lack formal structural explanations and predictive power. To address this gap, the study adopts a qualitative-descriptive approach, conducting a textual analysis of classical grammatical works and comparing them with modern theories of non-concatenative and templatic morphology, particularly as proposed by McCarthy and Watson. This comparison enables the reconstruction of core patterns within a more systematic and scalable model. The research further classifies verb forms into functional semantic categories and presents a visual schema that maps root-pattern structures from both perspectives. By bridging the descriptive richness of classical grammar with the formal abstraction of modern linguistics, this study offers an integrative framework with implications for Arabic language pedagogy and natural language processing (NLP). It contributes to more structured teaching methods and improved morphological modeling in computational applications.